L'AEROFOTOTECA NAZIONALE RACCONTA.... il gen. Petronio Malagoli - Gusmano, Stefano (GEOmedia, 2021)
General P. Malagoli was a founding father of modern defence aerial mapping in Italy. He also had a very distinctive personality and was a generous, bon vivant friend for many. In 2013 he made a gift to Aerofototeca Nazionale of his extraordinary professional/ scientific library: a great asset, for which AFN is truly grateful.